Remittances to LDCs: curse or panacea? - Rodríguez, Ennio (2013)
Remittances directly reduce poverty of recipient households, spur an increase in education and health expenditures, insure against adverse shocks, and finance housing and capital investments. However, they are not focused on the poorest countries or the poorest households or geographical regions as migration costs seem to discriminate against the poorest, and the environments of recipients are key to maximise development potential. Thus, remittances are neither a substitute for development assistance, debt forgiveness nor for public policies targeting the poor households and regions, rather, they can be a useful complement. Development assistance and public policies can be relevant for reaping the potential benefits of remittances; such interventions can be levied at the macro, meso and micro levels. Remittances can be used to secure further access to financial markets through: future-flow receivables securitisation; and, arranging remittance-based future-flow based syndicated medium to long-term loans.